Development and Validation of an Indonesian Culture Based Self Esteem Scale for Empty-Nest Older Adults Using the Rasch Model - Renidayati; Daharnis; Dina Sukma (Miracle Journal Get Press, 2026)
The empty-nest phase in later life is a family transition that may affect self-esteem, social relationships, meaning in life, and psychological well-being. However, self-esteem instruments specifically developed for empty-nest older adults within the Indonesian cultural context remain limited. Purpose: This study aimed to develop and validate the Indonesian Culture-Based Self-Esteem Scale for Empty-Nest Older Adults using the Rasch model to support assessment in Guidance and Counseling. Method: A quantitative instrument-development and validation design was employed. The participants were 213 empty-nest older adults in Padang Pariaman Regency, Indonesia, selected through purposive sampling, with an additional 30 older adults involved in the readability testing stage. Instrument development involved a literature review, construct formulation, item writing, expert validation, readability testing, main data collection, and Rasch psychometric analysis. Results: The results showed that of the initial 42 items, 36 were empirically tested and 32 final items were retained. Aiken’s V ranged from .78 to .96, with a mean of .88. Rasch analysis indicated ordered response categories, 32 model-fitting items, person reliability of .86, item reliability of .95, and Cronbach’s alpha of .89. Implications: The scale also showed adequate unidimensionality and no meaningful bias in most respondent groups. Conclusion: These findings imply that the developed scale is suitable as a Guidance and Counseling assessment instrument to identify the self-esteem of empty-nest older adults in a more contextual, valid, and culturally responsive manner.